İmam Muhammed'in el-Câmi‘u's-sağîr isimli eserine özgü meselelerin tespit ve tahlili - Civelek, Ercan (My University, 2021)
Hanefî mezhebinin kurucu metinleri içerisinde yer alan el-Câmi‘u’s-sağîr, kısaolmasıyla birlikte mezhebin ilk ve en hacimli kitabı olan el-Asl’a dikkate değer katkılarsunmaktadır. Bu katkıların izini sürmek amacıyla gerçekleşen bu araştırmada, el-Câmi‘u’ssağîr’de yer alan meseleler el-Asl ile mukayese edilerek üçlü bir tasnife tabi tutulmuştur. elAsl’da yer almayan el-Câmi‘u’s-sağîr meselelerini konu edinen birinci bölümde, kimi elCâmi‘u’s-sağîr meseleleri için şerhlerde zikredilen “havâss” nitelemeleri ayıklanarak el-Asl’dabulunmayan 134 meselenin tespiti yapılmıştır. İkinci bölümde, iki kitabın meselelerikarşılaştırılarak telif zamanı daha geç olan el-Câmi‘u’s-sağîr’in el-Asl’ın anlaşılmasına yönelikmuhtelif katkılar sunan 74 mesele zikredilmiştir. Üçüncü bölümde de, el-Câmi‘u’s-sağîr’defarklı bir hükümle zikredilen 20 meseleye yer verilmiş ve fıkıh kitaplarında daha sahih olduğuvurgulanan görüşe işaret edilmiştir. Böylece iki zâhiru’r-rivâye eseri arasındaki ilişkininboyutları ortaya konularak ilk fıkıh mezhebinin ortaya çıkış dönemindeki literatürününanlaşılmasına bir katkı sağlanması hedeflenmektedir.

Being among the founding texts of the Hanafi sect, al-Jami’as-Saghir, with its shortness,makes remarkable contributions to the first and most voluminous book of the sect, al-Asl. Inthis study, which was carried out in order to trace these contributions, the issues in al-Jami’asSaghir were compared with al-Asl and subjected to a triple classification. In the first chapter,which deals with the issues of al-Jami’as-Saghir, which are not included in al-Asl, thedescriptions of havâss mentioned in the commentaries for some al-Jami’as-Saghir issues havebeen eliminated and 134 issues not included in al-Asl have been identified. In the secondchapter, by comparing the issues of the two books, 74 issues that have been observed to havecontributed to the understanding of al-Asl from al-Jami’as-Saghir, whose copy time is later, arementioned. In the third part, 20 issues mentioned with a different provision in al-Jami’as-Saghirare included and the view emphasized to be more sound in fiqh books is pointed out. Thus, it isaimed to make a contribution to the understanding of the literature in the period of emergenceof the first fiqh sect by revealing the dimensions of the relationship between two Zahir alRiwayah works.
Keywords: al-Asl; al-Bazdawi; el-Asl Havass; el-Câmi‘u’s-sağîr; el-Jami’as-Saghir; Havâss; Islam; Islamic law; İslam; İslam hukuku; Pezdevî